Perancangan dan Penilaian Kinerja Kompor Berbahan Bakar Minyak Jelantah Berbasis Teknologi FFEAS Metode French - Setiawan, Rizal Justian; Ma'ruf, Khakam; Darmono; Khosyiati, Nur Evirda; Azizah, Nur (SPECTA Journal of Technology, 2025)
Waste cooking oil or used cooking oil is potentially carcinogenic waste and dangerous to human health if used for cooking repeatedly. If waste cooking oil is disposed of in the environment, it can harm soil structure by impeding water movement in soil pores. Therefore, the development of waste cooking oil stove technology designed using the French method can be a solution to utilize waste cooking oil as an alternative fuel. The results of this research are a stove design and device that can use used cooking oil. This stove uses abundant waste cooking oil with efficient and clean combustion results through the use of FFEAS Technology. This stove uses a floating wick and an excess air system which makes the combustion process easier. The performance of the stove being developed can be seen in several tests such as ignition combustion duration, required pressure, operational time, fuel consumption rate, sensible heat, and latent heat. The results of three tests that have been conducted show that the average ignition duration of the stove is 12 minutes, the optimal pressure is 4-5 bar, the fuel consumption rate is 8.34ml/minute, the average latent heat is 1,095.82 watts, and the average sensible heat is 132.48 watts.